Love attitudes of students with different attachment styles - Fourmanov, Igor A. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
The purpose of the article is to study the gender characteristics of the determination of students’ love attitudes by different attachment styles. The survey involved 1st–4th year students of various Belarusian universities (738 persons). The study rests on the «Love Attitudes Scale» by K. Hendrik and S. S. Hendrik, «Adult Attachment Scale» by N. L. Collins. It was found that in men, a secure attachment style is positively associated with the attitude eros, and negatively with ludus and storge; fearful attachment style positively associated with eros and agape, and negatively with ludus; preoccupied attachment style positively associated with pragma and mania, and negatively with eros; the dismissing style of attachment is positively associated with ludus, and negatively with eros and agape. In women, only preoccupied attachment style is positively correlated with mania and agape attitudes. It was shown that in men, a secure attachment style is a negative predictor of storge; fearful attachment style is a positive predictor of mania, preoccupied attachment style is a positive predictor of mania, agape, pragma and a negative predictor of eros, dismissing attachment style is a positive predictor of ludus and a negative predictor of agape and eros. Women’s love attitudes are less influenced by attachment styles – only fearful attachment style is a positive predictor of mania, and preoccupied attachment style is a positive predictor of mania and agape.